Perencanaan Struktur Gedung Sekolah Tinggi di Magelang (Indonesian Journal of Civil Engineering Study, 2025)
That has a significant impact on economic development. Magelang has the opportunity because it is the first choice for thousands of new students from various regions in Indonesia who want to continue their studies at university. The College Building is a building consisting of lecture rooms, laboratories, meeting rooms, and lecturer rooms. As the number of students increases, there is an increasing demand for expanded physical buildings to accommodate a wide range of activities. With the construction of this building, it is hoped that it can have an international standard building by providing very good and comfortable facilities. The Planning of the Structure of Higher Education Buildings in Magelang refers to the regulations of the (SNI) Standard National Indonesian, Structural Concrete for Building Buildings SNI 2847-2019, Earthquake Resistance Planning for Building and Non;building Structures" SNI 1726-2019. Minimums and Criteria for Buildings and Other Structures" (SNI 1727-2020). The structural design of Magelang High School Building covers both upper and lower structures. The upper structure, planned using ETABS V.18 and Sp Column software, includes roofs, slabs, beams, and columns, The upper part deals with architectural design, whereas the lower part pertains to foundation preparation.Different loads are considered in structural analysis, including dead loads, live loads, wind loads, and earthquake loads. The design encompasses roof plates, floor plates, beams, columns, stairs, and foundations, with concrete quality targeted at fc' 33 MPa and steel quality at fy 420 MPa. The planning resulted in 4 block types (B1, B2, B3, and B4), 3 column types (K1, K2, and K3), and 5 floor plate types (A, B, C, D, and E). The foundation for the lower structure consists of pile foundations with a diameter of 50 cm.
Keywords: Structural Planning; School Building; Building Structure